2013
DOI: 10.1590/s2317-17822013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Do body mass index and fat volume influence vocal quality, phonatory range, and aerodynamics in females?

Abstract: PURPOSE: To analyze the impact of body weight and body fat volume on selected parameters of vocal quality, phonatory range, and aerodynamics in females. METHODS: Based on measurements of body mass index in combination with body fat volume, 29 normophonic female subjects were classified as normal weight, underweight, and obese. Voice quality was investigated via auditory-perceptual ratings of breathiness, roughness, and overall dysphonia severity, via various acoustic measures and a multiparametric index. Phona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 22 publications
2
33
1
4
Order By: Relevance
“…There was a statistically significant difference in MPT values for the vowels [a], [i], and [u] before and after bariatric surgery (Table 1), which corroborates with the findings of other authors [7][8][9]15] who found a reduction in this parameter in individuals with obesity. This result can be explained by the presence of fat in the neck in obese individuals, which predisposes the increase in type II muscle fibers in the dilator muscles of the upper airways, causing lower respiratory muscle strength [17] and difficulty in mobilizing the airflow to the same degree as in non-obese individuals.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…There was a statistically significant difference in MPT values for the vowels [a], [i], and [u] before and after bariatric surgery (Table 1), which corroborates with the findings of other authors [7][8][9]15] who found a reduction in this parameter in individuals with obesity. This result can be explained by the presence of fat in the neck in obese individuals, which predisposes the increase in type II muscle fibers in the dilator muscles of the upper airways, causing lower respiratory muscle strength [17] and difficulty in mobilizing the airflow to the same degree as in non-obese individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Acoustic analysis revealed higher fundamental frequency (f0) and reduced maximum phonation time (MPT). Other studies of morbidly obese women have found reduced maximum phonation time [8,9] and low fundamental frequency values by female standards [8].…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations